Dualisme Putusan Peradilan Tentang Batas Minimum Usia Calon Kepala Daerah pada Pilkada 2024 - Muhammad Fajar Rizki (Fakultas Hukum Universitas Islam Indonesia, 2025)
Abstract This study aims to analyze the regulation of the minimum age limit for regional head candidates after the dualism of judicial decisions regarding the minimum age limit for regional head candidates (open legal policy) between the Constitutional Court and the Supreme Court. The problems studied consist of: First, the construction of the two judicial decisions regarding the minimum age limit for regional head candidates. Second, the problems caused by the dualism of judicial decisions on the norms that are open legal policy. Third, future arrangements regarding the age of regional head candidates. This research uses normative legal research methods, so this research uses a statutory approach and a case approach. The results of this study show that between the two judicial decisions there are different methods of interpretation and configuration, as well as in the application of methods of interpretation that are closely related to the authority of the legislature (open legal policy). In addition, the dualism of these judicial decisions raises a variety of issues, ranging from regulatory issues, interpretation issues, to legal certainty issues. The results of further research show that the dualism of decisions cannot be avoided due to the dualism of judicial review authority by these two judicial institutions which has the potential to cause various kinds of problems including not providing guarantees of legal certainty, conflicting judicial decisions, to cause permits to be issued.